Longitudinal Fecal Microbiota Profiles in A Cohort of Non-Hospitalized Adolescents and Young Adults with COVID-19: Associations with SARS-CoV-2 Status and Long-Term Fatigue - Christine Olbjørn; Milada Hagen; Aina Elisabeth Fossum Moen; Lise Beier Havdal; Silke Lauren Sommen; Lise Lund Berven; Espen Thiis-Evensen; Tonje Stiansen-Sonerud; Joel Selvakumar; Vegard Bruun Bratholm Wyller (Pathogens)
Adolescents most often experience mild acute COVID-19, but may still face fatigue and persistent symptoms such as post-COVID-19 condition (PCC) and post-infective fatigue syndrome (PIFS). We explored the fecal microbiota of SARS-CoV-2 positive and negative non-hospitalized adolescents and young adults (12–25 years of age) in the “Long-Term Effects of COVID-19 in Adolescents” (LoTECA) project, a longitudinal observational cohort study. With a targeted qPCR approach, the quantities of 100 fecal bacterial taxa were measured at baseline (early convalescent stage) in 145 SARS-CoV-2-positive and 32 SARS-CoV-2 negative participants and after six months in 107 of the SARS-CoV-2-positive and 19 of the SARS-CoV-2 negative participants. Results: Faecalibacterium prausnitzii M21.2 and Gemmiger formicilis (both p < 0.001) were enriched in the SARS-CoV-2-positive participants compared to negative controls at baseline. In SARS-CoV-2-positive participants, lower baseline abundance of Faecalibacterium prausnitzii M21/2 (p = 0.013) and higher abundance of Clostridium spiroforme (p = 0.006), Sutterella wadsworthensis (p < 0.001), and Streptococcus thermophilus (p = 0.039) were associated with six-month fatigue. Sutterella wadsworthensis and Streptococcus thermophilus enrichment was additionally associated with PCC in the SARS-CoV-2-positive group (p < 0.001 and 0.042 respectively). Conclusions: Adolescents and young adults with mild acute COVID-19 infection had increased fecal abundance of the beneficial Faecalibacterium prausnitzii M21/2 and Gemmiger formicilis compared to SARS-CoV-2 negative controls in the early convalescent stage. Additionally, the abundance of both known (Faecalibacterium prausnitzii, Streptococcus thermophilus) and new (Clostridium spiroforme, Sutterella wadsworthensis) bacteria were associated with persistent symptoms such as fatigue in the COVID-19 infected group, warranting further exploration of the role of these bacteria in COVID-19 disease and PCC pathophysiology.